2011
DOI: 10.1603/ec10197
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Male and Female Emerald Ash Borer (Coleoptera: Buprestidae) Responses to Phoebe Oil and (<I>Z</I>)-3-Hexenol Lures in Light Green Prism Traps

Abstract: We conducted trapping experiments for the emerald ash borer, Agrilus planipennis Fairmaire (Coleoptera: Buprestidae) in Michigan, U.S.A., and Ontario, Canada, to compare unbaited light green sticky prism traps with traps baited with phoebe oil, (Z)-3-hexenol (Z3-6:OH), or blends of other green leaf volatiles (GLVs) with Z3-6:OH. Traps were placed in the lower canopy of ash trees (Fraxinus spp.). Catches with Z3-6:OH-baited traps showed a significant male bias and these traps caught significantly more males tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 13 publications
1
44
0
Order By: Relevance
“…The average time from infestation to detection is 6-12 years (McCullough et al 2011;MFK unpublished data), ample time for the beetles to become firmly established in a new location. Much research and resources have been devoted to developing survey techniques to shorten the time between infestation and detection (Francese et al 2006;Poland et al 2006;Crook et al 2009;Francese et al 2011;Grant et al 2011;McCullough et al 2011;Ryall et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The average time from infestation to detection is 6-12 years (McCullough et al 2011;MFK unpublished data), ample time for the beetles to become firmly established in a new location. Much research and resources have been devoted to developing survey techniques to shorten the time between infestation and detection (Francese et al 2006;Poland et al 2006;Crook et al 2009;Francese et al 2011;Grant et al 2011;McCullough et al 2011;Ryall et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Two types of host volatiles have been demonstrated to be attractive to adults: green leaf volatiles Rodriguez-Saona et al 2006;de Groot et al 2008;Grant et al 2010Grant et al , 2011 and bark sesquiterpenes McCullough 2006, Crook et al 2008). Of the green leaf volatiles, one compound in particular, (3Z)-hexenol, is highly antennally active and attractive to males (de Groot et al 2008, Grant et al 2010, Silk et al 2011.…”
mentioning
confidence: 99%
“…(3Z)-Hexenol does appear to have an important role in host and/or mate Þnding by males (de Groot et al, 2008;Grant et al, 2010Grant et al, , 2011 while increased bark sesquiterpene emissions are indicative of a stressed tree and likely have an important role for oviposition by females . Our results on purple traps (experiment 1) showed that traps baited with the 80/20 manuka/phoebe oil caught more A. planipennis than those baited with manuka oil.…”
Section: Discussionmentioning
confidence: 99%
“…On light green prism traps (3Z)-hexenol release rates of 7.6 and 80 mg per day caught signiÞcantly more males than females, and more males than the unbaited controls or manuka oil baited traps. Lures containing phoebe oil and (3Z)-hexenol were tested with light green prism traps by Grant et al (2011). They found that light green prism traps hung in the canopy baited with (3Z)-hexenol captured more males than females and signiÞcantly more males than unbaited traps.…”
mentioning
confidence: 99%